Deep Anterior Lamellar Keratoplasty in Eyes With Intrastromal Corneal Ring Segments. Issue 5 (May 2019) - Ravera, Vittoria; Bovone, Cristina; Scorcia, Vincenzo; D'Angelo, Sergio; Busin, Massimo
Abstract : Purpose: To evaluate the possibility of using the intrastromal corneal ring segments (ICRSs) previously implanted as a depth reference for performing pneumatic dissection in deep anterior lamellar keratoplasty (DALK). Methods: The depth of placement of 2 symmetrical ICRSs placed in the superior and inferior midperipheral cornea of 4 eyes of 4 patients with keratoconus was measured by means of anterior segment optical coherence tomography. Because of irregular and/or high astigmatism, DALK using pneumatic dissection was performed in all eyes. The standardized procedure included the following: 1) Deep trephination of the recipient cornea outside the ICRSs (9 mm in diameter), aimed at facilitating the insertion and advancement of a dedicated cannula under the ICRS implant, just within its peripheral margin; 2) air injection for pneumatic dissection; 3) removal of about 80% of the anterior stroma; 4) perforation of the "big bubble" ceiling under viscoelastic protection and removal of its central 6 mm; and 5) suturing of a donor lamella of the anterior stroma obtained by microkeratome dissection using a 450-μm head and punched to a diameter of 9 mm. Results: In all cases, the site for air injection was selected where the thickness of the stroma underlying the superior ICRS did not exceed 150 μm. Pneumatic dissection succeeded uneventfully in all eyes; postoperative best spectacle-corrected visual acuity was 20/20 in 3 of 4 eyes, whereas refractive astigmatism was less than 3 diopters in all cases. Conclusions: The presence of ICRSs facilitates gauging the depth of cannula insertion at the time of DALK, to succeed with pneumatic dissection. Abstract : Supplemental Digital Content is Available in the Text.